Pengembangan E-Booklet Berbasis Realistic Mathematics Education pada Materi Peluang untuk Kelas VIII - Satiti, Wisnu Siwi; Khotimah, Khusnul; Elchisby, Imarotul Ariza; Hidayatulloh, Faisol (Universitas KH. A. Wahab Hasbullah, 2023)
Mathematical concepts cannot be separated from real context that we face daily. Therefore, mathematics classroom should involve application of mathematical concepts in solving real-life problems. However, this practices generally only prioritizes on process of mathematizing real-life problems into mathematical form. This makes students experience difficulties in understanding and applying mathematical concepts to real-life. One learning approach that facilitates the use of real-life contexts in learning is Realistic-Mathematics-Education (RME). Apart from that, learning can be assisted using learning media. Therefore, this study aims to develop learning media in the form of an electronic booklet (e-booklet) for learning probability at 8th grade. This study employs Research and Development method by applying ADDIE model. The results show that the E-Booklet received an expert assessment in the Very Valid category (87%). Meanwhile, the assessment on the media aspect obtained a score of 85.5% in the Very Valid category. The results of filling out the student response questionnaire obtained an average of 80.12% and were in the practical category. The N-Gain Pre-Test and Post-Test results show that the e-booklet obtains 82% which is in effective category. This shows that the e-booklet is effective in supporting students' understanding the mathematics concepts.